Pengaruh Pemberian Jus Sambung Nyawa (Gynura procumbens L. merr) Terhadap Produksi Ayam Pedaging - Nata Dian Nanda; Edya Moelia Moeis; Eddy Trijana Sujdani (Universitas Islam Balitar, 2017)
The objective of this study was to determine the effect off sambung nyawa (Gynura procumbens) juice in drinking water on broiler performance (feed consumption, aver-ege daily gain, feed conversion and persentasion carcass). The research is used 200 broiler Hybro strains from PT. Manggis, were allocated into 4 treatments and 5 replications consisting of 10 broiler. Maintenance of the chicken is done for 28 days. The treatment was juice sambung nyawa with each concentration : T0 (without the addition of sambung nyawa juice), T1 (addition of 10 sambung nyawa juice in 1000 ml of drinking water), T2 (addition of 20 sambung nyawa juice in 1000 ml of drinking water) and T3 (addition of 30 sambung nyawa juice in 1000 ml of drinking water). Parameters observed in this study is broiler performance (feed consumption, aver-ege daily gain, feed conversion and persentasion carcass). The result from a completely randomized design were analyzed using ANOVA (Analysis of Variance / ANOVA) and if significant difference test followed by Duncan continued. The result showed that the addition of sambung nyawa juice at different levels (10, 20 and 30 ml) in the drinking water of broilers was highly did not affect (P > 0.05) on broiler performance (feed consumption, aver-ege daily gain, feed conversion and persentasion carcass).Keyword : Sambung Nyawa Juice, Performance Broiler.